Crack initiation and early propagation in case hardened sintered PM steels under cyclic load. (15th March 2023) - Holmberg, Anders; Wiklund, Urban; Isaksson, Per; Kassman Rudolphi, Åsa
ABSTRACT: In the present study, crack propagation through the case hardened region of two different PM steels manufactured with different powder size distributions and sintered at different temperatures has been investigated. EBSD was used to study the microstructure before and after case hardening, revealing the relationship between powder particle grains after sintering and prior austenite grains after case hardening. A novel approach was used to achieve short cracks (10–20 µm) with high repeatability. The cracks were then analysed using EBSD and SEM, revealing detailed and novel information about the crack propagation route in the materials. Both tested materials show the same crack propagation behaviour. If a prior grain/prior austenite boundary is present within an angle from the crack initiation site, the cracks will follow the boundary and thus propagate intergranular, suggesting that the preferred route of crack propagation in case hardened sintered steel is along these boundaries.